The Historical and Cultural Value of RC Constructions and the Main Critical Issues for Rehabilitation - Marco Vona; Benedetto Manganelli (Infrastructures, 2022)
In recent years, the preservation strategies of cultural heritage have become an element of considerable importance. Unfortunately, research has often been conducted in an excessively mono-sectoral or disaggregated manner. Moreover, there is a significant number of reinforce concrete (RC) buildings and engineering works that are of historical interest and play a key role during the earthquakes. An urban center, its historical structures and infrastructures or single buildings, if well managed, preserved, protected, recovered and enhanced can represent an excellent source of income and induce a considerable economic development in the neighboring areas. On the other hand, a lack of value appreciation and/or incorrect management represent a significant economic loss in the long-term, but an immediate loss after earthquakes. In this work, the historical and cultural value of these RC structures and infrastructures is discussed and the main critical issues are identified, outlining the fundamental requirements for conservation.